The fever : a novel - Abbott, Megan., 1971- (Little, Brown & Co., 2014)
"The panic unleashed by a mysterious contagion threatens the bonds of family and community in a seemingly idyllic suburban community. The Nash family is close-knit. Tom is a popular teacher, father of two teens: Eli, a hocky star and girl magnet, and his sister Deenie, a diligent student. Their seeming stability, however, is thrown into chaos when Deenie's best friend is struck by a terrifying, unexplained seizure in class. Rumors of a hazardous outbreak spread through the family, school and community. As hysteria and contagion swell, a series of tightly held secrets emerges, threatening to unravel friendships, families and the town's fragile idea of security" --